Nematode Management for Bedding Plants - William T. Crow (EDIS)
Florida is the “land of flowers.” Surely, one of the things that Florida is known for is the beauty of its vegetation. Due to the tropical and subtropical environment, color can abound in Florida landscapes year-round. Unfortunately, plants are not the only organisms that enjoy the mild climate. Due to warm temperatures, sandy soil, and humidity, Florida has more than its fair share of pests and pathogens that attack bedding plants. Plant-parasitic nematodes can be among the most damaging and hard-to-control of these organisms. This revised 11-page fact sheet was written by William T. Crow and published by the UF Department of Entomology and Nematology, February 2014.